Cost Overrun Factors Involving Local Private Residential - Fatma Arisya Nik Yahya, Nik; S.K, Suhaida; Aini Osman, Nurul; Abdul Razak, Nadeera (International Journal of Engineering and Technology, 2018)
Cost is the prime factor for driving to the successful of a project. A poor cost performance become a common problem in worldwide which bring a significant financial risk to both contractors and clients. Construction projects are relatively risky because the projects operate in a complexity and dynamic situation. This study aimed to explore the major contributors of cost overrun and propose strategies in minimizing the cost overrun factors involving local private residential projects in Malaysia. A quantitative method was applied to the respondents from contractors firm Grade G7 in Selangor area, and the data were analyzed using Likert scale to obtain mean score. There are 5 categories of cost overrun factors found from previous studies. Design error and poor contractors site supervision were ranked as the top two contributors to cost overrun in Private Residential Projects. Additionally, 79% of the respondents agreed that construction projects face cost overrun with an average amount of 1-5% of contract sum. 9 strategies are available to overcome the problems and the result shows that effective strategic planning is the most effective mitigation.Â